Impact of the Chelsea critical care physical assessment (CPAx) tool on clinical outcomes of surgical and trauma patients in an intensive care unit: An experimental study - Megan Whelan; Heleen Van Aswegen; Evelyn Corner (AOSIS, 2018)
Background: Critically ill patients following traumatic injury or major surgery are at risk of loss of skeletal muscle mass, which leads to decreased physical function. Early rehabilitation in an intensive care unit (ICU) is thought to preserve or restore physical functioning. The Chelsea critical care physical assessment (CPAx) is a measurement tool used to assess physical function in the ICU. Objectives: To determine whether the use of the CPAx tool as part of physiotherapy patient assessment, in two adult trauma and surgical ICU settings where early patient mobilisation forms part of standard physiotherapy practice, had an impact on ICU and hospital length of stay (LOS) through delivery of problem-oriented treatment plans. Method: A single-centred pre-post quasi-experimental study was conducted. The population was a consecutive sample of surgical and trauma ICU patients. Participants' functional ability was assessed with the CPAx tool on alternative days during their ICU stay, and rehabilitation goals were modified according to their CPAx score. Intensive care unit and hospital LOS data were collected and compared to data of a matched historical control group. Descriptive and inferential statistics were used. Results: A total of 26 ICU patients were included in the intervention group (n = 26). They received CPAx-guided therapy, and outcomes were matched with ICU patients in the historical control group (n = 26). The median sequential organ failure assessment (SOFA) score was significantly higher in the control group (p = 0.005) (3.5 [IQR 2-6.3]) versus (2 [IQR 1.8-2.5]) for the intervention group. The median admission CPAx score for the intervention group was 33.5 (IQR 16.1-44), and the median ICU discharge score was 38 (IQR 28.5-43.8). No significant differences were found in ICU days (control 2.7 [IQR 1.1-5.2]; intervention 3.7 [IQR 2.3-5.4]; p = 0.27) or hospital LOS (control 13.5 [IQR 9.3-18.3]; intervention 11.4 [IQR 8.4-20.3], p = 0.42). Chelsea critical care physical assessment scores on ICU admission had a moderate negative correlation with hospital LOS (r = −0.58, p = 0.00, n = 23). Chelsea critical care physical assessment scores at ICU discharge had strong positive correlation with discharge SOFA scores (r = 0.7; p = 0.025; n = 10). Conclusion: Problem-oriented patient rehabilitation informed by the CPAx tool resulted in improvement of physical function but did not reduce ICU or hospital LOS. Clinical implications: A higher level of physical function at ICU admission, measured with CPAx, was associated with shorter hospital LOS.